ANALISIS NILAI EKONOMI TAMBANG INKONVENSIONAL (TI) DENGAN KEGIATAN PERIKANAN TANGKAP DAN PARIWISATA DI PESISIR TANJUNG ULAR KABUPATEN BANGKA BARAT - ENDANG BIDAYANI (Department of Aquatic Resources Management, Faculty of Agriculture, Fisheries, and Biology, University of Bangka Belitung, 2009)
Tin production in Kabupaten Bangka Barat (Bangka Belitung Province) generated positive and negative impact to environment. The aim of this research is to analyse environmental impact from illegal minning (TI) activity to fishing capture and tourism activity in Tanjung Ular Coastal area, Kabupaten Bangka Barat. The data was analysed by two methods : first, analysis of impact, and second, fishing capture values and tourism value analysis. The results shows that the illegal minning causes consumer sutplus of fishing capture is 7.466.722.522,22/ha/year, economic value of tourism activity is Rp 8.761.814.654.000,00, and consumer surplus of illegal minning is Rp. 4.045.751.071,2/ ha/year in ten years (1998-2008). The policy of fishery sector development is to stop illegal minning in the fishery area, and changed to marine tourism activity.